The Influence Of Layoffs, Workload And Financial Compensation On Job Satisfaction And Its Impact On Employee Performance At Sirclo Group Jakarta - Febri Hariyanto; Edi Sugiono; Suryono Efendi (Ridwan Institute, 2023)
This study aims to analyze the effect of layoffs, workload and financial compensation on job satisfaction and its impact on employee performance. The independent variables used are layoff (X1), workload (X2), financial compensation (X3), the dependent variable is employee performance (Y) with the intervening variable is job satisfaction (Z). The research approach used is quantitative research by means of observation, interviews, and surveys. The analysis model uses SEM software AMOS version 23. Survey-based data collected from 130 respondents. The study found that layoff has a positive and significant effect on job satisfaction, workload has a negative and significant effect on satisfaction, financial compensation has a positive and significant effect on job satisfaction, layoff has a negative and significant effect on employee performance, workload has a positive and significant effect on employee performance, financial compensation has a positive and significant effect on employee performance, layoff has a positive and significant effect on employee performance through job satisfaction, workload has a negative and significant effect on employee performance through job satisfaction, financial compensation has a positive and significant effect on employee performance through job satisfaction. Job satisfaction has a positive and significant effect on employee performance.